Variation and asymmetry in host-symbiont dependence in a microbial symbiosis - Minter, Ewan J. A. (BMC Evol Biol, 2018)
BACKGROUND: Symbiosis is a major source of evolutionary innovation and, by allowing species to exploit new ecological niches, underpins the functioning of ecosystems. The transition from free-living to obligate symbiosis requires the alignment of the partners’ fitness interests and the evolution of mutual dependence. While symbiotic taxa are known to vary widely in the extent of host-symbiont dependence, rather less is known about variation within symbiotic associations. RESULTS: Using experiments with the microbial symbiosis between the protist Paramecium bursaria and the alga Chlorella, we show variation between pairings in host-symbiont dependence, encompassing facultative associations, mutual dependence and host dependence upon the symbiont. Facultative associations, that is where both the host and the symbiont were capable of free-living growth, displayed higher symbiotic growth rates and higher per host symbiont loads than those with greater degrees of dependence. CONCLUSIONS: These data show that the Paramecium-Chlorella interaction exists at the boundary between facultative and obligate symbiosis, and further suggest that the host is more likely to evolve dependence than the algal symbiont. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12862-018-1227-9) contains supplementary material, which is available to authorized users.